A moving average S control chart for monitoring process variability. Issue Volume 28:Issues 2(2016) (2nd April 2016) - Adeoti, Olatunde A.; Olaomi, J. O.
ABSTRACT: An efficient alternative to the S control chart for detecting shifts of small magnitude in the process variability using a moving average based on the sample standard deviation s statistic is proposed. Control limit factors are derived for the chart for different values of sample size and span w . The performance of the moving average S chart is compared to the S chart in terms of average run length. The result shows that the performance of moving average S chart for varying values of w outweigh those of the S chart for small and moderate shifts in process variability.